Examining the Impact of Customer Value and Customer Experience on Customer Loyalty with Satisfaction as a Mediating Variable: Evidence from State-Owned Syariah Banking - Onad Sudirjo; Rachel Juwita Sari; Doni Sindoro (PT. Mawadaku Sukses Solusindo, 2026)
This study aims to examine the effect of Customer Value and Customer Experience on Customer Loyalty, with Customer Satisfaction functioning as an intervening variable within the context of Islamic banking customers. The research is grounded in the growing recognition of customer loyalty as a critical determinant in sustaining competitiveness within the increasingly dynamic Islamic financial services sector. A quantitative research approach was employed, with primary data gathered a structured questionnaire survey. The collected data were subsequently processed using multiple linear regression analysis along with the Sobel test to assess the mediating effect of Customer Satisfaction. The findings indicate that both Customer Value and Customer Experience exert a positive and statistically significant influence on Customer Satisfaction, with Customer Experience identified as the more dominant predictor (β = 0.572). In addition, the analysis reveals a strong direct impact of Customer Value, Customer Experience, and Customer Satisfaction on Customer Loyalty. The role of Customer Satisfaction as a partial mediating variable in the relationships between Customer Value and Loyalty as well as between Customer Experience and Loyalty, is empirically validated. From a managerial perspective, the study suggests that Islamic banking institutions should prioritize the development of comprehensive customer experience management strategies and strengthen product value propositions in order to enhance customer loyalty through increased satisfaction levels.